Pemanfaatan Media Sosial Instagram dalam Membangun Brand Image Wardah sebagai Produk Kosmetik Halal di Indonesia - Fadiah Cahya Amelia; Arfian Suryasuciramdhan; Ika Choirunnissa; Risti Septyani; Mario Maulana (Pusat Riset dan Inovasi Nasional, 2025)
The main problem discussed in this research is how digital communication strategies through social media, especially Instagram, can be effectively utilized to build the brand image of halal cosmetic products amidst increasingly fierce competition in the beauty industry. Wardah was chosen as the object of study because of its success in positioning itself as a pioneer of halal cosmetics in Indonesia, with an approach that emphasizes Islamic values. This study aims to examine the role of digital communication strategies in shaping the halal brand image of Wardah cosmetic products through the Instagram platform. As one of the local brands that carries Islamic values, Wardah utilizes social media as the main means to reach consumers, especially the modern Muslimah segment. The approach used in this research is descriptive qualitative with content analysis method, which focuses on visual narratives, captions, audience engagement, and collaboration with influencers. The results showed that Wardah consistently displays content that represents the values of halalness, simplicity, and modern and professional Islamic beauty. Through an integrated communication strategy, Instagram is not only a promotional medium, but also a means of forming a strong brand image that is relevant to the identity of the target audience. The findings underscore the importance of visual and narrative communication in strengthening the positioning of halal products in the Indonesian cosmetics market.